AMA activities in developing education essentials - Correspondence: Howard to Anlyan, et.al. - Howard, D. Robert (1971)
A memorandum sent to Duke Administrators from Dr. Robert Howard dated August 17, 1971 updating them on progress made by the AMA to develop Educational Essentials for the assistant to the primary care physician. Dr. Howard refers readers to the attached draft essentials included in minutes of the subcommittee to draft essentials that met in Chicago August 3-4, 1971. The emphasis will be to train a generalist and specialization can be taught and certified later by other groups.